Crossing continents : between India and the Aegean, from prehistory to Alexander the Great - Arnott, Robert, 1951- (Oxbow Books, 2022)
The first contacts between Greece, the Aegean and India are generally thought to have occurred at the beginning of the sixth century BC. There is now, however, growing evidence of much earlier but indirect connections, reaching back into prehistory. These were initially between India and its Indus Civilisation (Meluhha) and the Near East and then finally with the societies of the Early and Middle Bronze Age Aegean,with their slowly emerging palace-based economies and complex social structures. Starting in the middle of the third millennium BC but diminishing after approximately 1800 BC, these connections point to a form of indirect or what might be called 'trickle-down' contact between the Aegean and India. From the start, until 2500 BC, the objects and commodities that formed this contact were transported overland, through Northern Iran, but after that time, the Harappans took control and we see a structured trade using the sea out through the Persian Gulf.0These contacts can also be placed into three categories: (a) the importation of objects manufactured in India or made from Indian commodities imported into the Near East,which eventually found their way to the Aegean and have parallels at Indian sites; (b) the importation of inorganic commodities such as tin, possibly some gold and lapis lazuli, exported from India or Central Asia under Harappan control; and (c) the importation of non-perishable organic commodities.0This study views the Aegean as part of a greater trade network and here the author has attempted to both evaluate and re-evaluate what evidence and speculation there are for such contacts, particularly for the commodities such as tin and lapis lazuli as well as more recently discovered objects.